An Intensive Monitoring of Adverse Drug Reactions in Indoor Patients of Paediatric Department at Tertiary Care Teaching Hospital in Gujarat, India. - Kandarp Patel; Kuntal Thacker; Neeta Kanani; Vimesh Mistry (Pharmacology and Clinical Pharmacy Research, 2021)
they differ from adults in pharmacokinetic and pharmacodynamics responses. ADRs reported in adults do not predict those in children. Thus, this study aimed to intensively monitor ADRs occurred in inpatients of paediatric department of tertiary care teaching hospital to assess the same in terms of incidence, causality, severity and preventability. A prospective observational single centre study was done in the paediatric department of SSG hospital, Vadodara over duration of 8 months. The ADRs were actively monitored and collected reports were analysed for ADR pattern, demographic proﬁle, causality, severity, and preventability. A total of 66 ADRs were documented during the period of 8 months. Among these 53.03% ADRs occurred below the age of 1 year, 89.13% ADRs occurred due to antibiotics, 56.06% ADRs are of Diarrhoea and vomiting and 80.43% ADRs developed after receiving drug intravenously. As per WHO-UMC criteria, 46.96 % ADRs were of probable while 51.51% ADRs were of possible causality while as per Naranjo scale 60.61% ADRs were of probable and 39.39% ADRs were of possible category. As per severity scale 69.70% reactions were mild and 30.30 % reactions were moderate. Probably preventable ADRs were about 57.58%. ADRs occurred more among infants and antibiotics were more commonly implicated. Most of the reactions were of mild severity and were probably preventable. Certain Precautionary measures can lead to significant prevention of ADRs in paediatric patients.